2003
DOI: 10.1097/01.smj.0000077011.58103.c1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Attitudes Regarding Physical Characteristics of Family Practice Physicians

Abstract: Our findings support the results of both studies published two decades earlier and more recently. Patients prefer a traditionally dressed physician as opposed to one who is dressed more casually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 7 publications
6
27
0
8
Order By: Relevance
“…Results of our study somehow similar to that performed by Keenum et al 23 and Najafi et al 13 . The reason could be because our patients are very curious in knowing the treating physian name.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results of our study somehow similar to that performed by Keenum et al 23 and Najafi et al 13 . The reason could be because our patients are very curious in knowing the treating physian name.…”
Section: Discussionsupporting
confidence: 83%
“…The reason could be because our patients are very curious in knowing the treating physian name. Regarding the wearing of stethoscope, 72.6% of our patients, mainly well educated, replied that doctors should wear stethoscope which is similar to study performed by Keenum et al 23 79.3% of our patients, who were mostly well educated, gave the reason that it is required for patients examination while rest replied that it is required for identification. Reasons regarding not wearing stethoscope, our patients replied that it causes cross infection and it may not be required for all the doctors.…”
Section: Discussionsupporting
confidence: 68%
“…2,4,11,12 Additionally, McKinstry et al 13 carried out a study in a family medicine setting, found that a majority of patients favored a male doctor wearing a formal suit and tie. Also, Keenum et al 14 carried out a study in a family practice setting, and observed that the majority of them favored a formal over a casual appearance for a family physician. Rehman et al reported that 76.3% of patients in USA favored the use of professional attire, including a white coat.…”
Section: Results:-mentioning
confidence: 99%
“…Daha önce yapılan çalışmalardaki bulguları destekler şekilde bu çalışmadaki çocukların, aynı cinsiyetteki diş hekimi tarafından tedavi edilmeyi tercih etmesi istatistiksel olarak anlamlı bulunmuştur (p<0.001) (42)(43)(44). Bununla beraber bu bulgunun, yapılan bazı çalışmalardaki bulgularla benzeşmediği görülmüştür (45,46). Ancak aynı cinsiyete göre çocukların diş hekimi tarafından tedavi edilmesi, dental klinikte tedavi kalitesini artırabilir.…”
Section: Tartiġmaunclassified